2008
DOI: 10.1016/j.puhe.2007.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Injecting drug use is associated with HIV risk perception among Mexican Americans in the Rio Grande Valley of South Texas, USA

Abstract: Objectives-Injection drug use (IDU) remains an actual risk variable in HIV infection in most ethnic populations and the association between actual risk and individual perception of HIV risk varies across studies and samples. This study aimed to examine the relationship between IDU and HIV risk perception among Mexican Americans residing in Rio Grande Valley, South Texas.Study Design-A cross-sectional study of IDU as a predictor of HIV risk perception.Methods-We assessed 275 participants (IDU = 11.9%, non-IDU =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Thus, it is unlikely that the number of syringes obtained through the program is sufficient to meet their needs. Since perceived susceptibility to acquiring HIV and perceived barriers to engaging in safe injection practices are the two most significant individual constructs in determining behavior change [28]. Our results highlight an important factor of ‘perceived barriers to obtaining sterile syringes’ that could be addressed by expanding the services provided by the local SEP.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, it is unlikely that the number of syringes obtained through the program is sufficient to meet their needs. Since perceived susceptibility to acquiring HIV and perceived barriers to engaging in safe injection practices are the two most significant individual constructs in determining behavior change [28]. Our results highlight an important factor of ‘perceived barriers to obtaining sterile syringes’ that could be addressed by expanding the services provided by the local SEP.…”
Section: Discussionmentioning
confidence: 89%
“…Deportees in our study injected for ~17 years. Having an extended history of drug use has been linked with a decreased perceived susceptibility to HIV infection (Essien et al, 2008) and may be indicative of having an extensive social network of drug users. Social networks composed of IDUs can produce normative risk perceptions surrounding drug use practices where risky behaviours are no longer viewed as such (Costenbader, Astone, & Latkin, 2006; Friedman & Aral, 2001; Kowalewski, Henson, & Longshore, 1997; Latkin, Sherman, & Knowlton, 2003; Renn, 1998; Rhodes et al, 2005; Wagner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This in part may help explain the high proportion of inconsistent condom use among IDUs with their steady female partners. Another study among Mexican drug users in Texas found that married participants were twice as likely to perceive being at risk for HIV than non-married participants (Essien et al, 2008). Additional research on migrants’ post-repatriation social networks and the role of partners is needed in order to better understand HIV risk perceptions among this population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations